EXPERIMENTAL DETERMINATION OF THE RATES OF NUCLEATION AND OF GROWTH OF PHASE TRANSFORMATION CENTERS - Yu. А. Taran; М. К. Zakharov; А. L. Тaran; R. N. Ivanov (Тонкие химические технологии, 2016)
The processes of granulation by crystallization of molten droplets in the flow of a cooling agent (prilling) and on the cooled surfaces of the granulators are widely used in the chemical and allied industries. The process of granulation (crystallization) of melts and qualitative indicators of granular products, their marketability is determined by the transfer phenomena in the phases and by the kinetics of crystallization and enantiotropic polymorphic transformations in the crystalline phase. Quantitatively the latter are given in the form of dependences of the rate of nucleation and growth of centers of transformation. The processes kinetics is usually less studied, but it determines the structure of the formed crystal phase and the maximum rate of the process. Therefore, most attention is focused on its study. The description of the scheme, of developed experimental laboratory facilities for the study of the rates of nucleation and growth of crystallization centers in the polycrystalline front of the growing group of crystals, as is the case when crystallization occurs in devices in real conditions (constrained growth of crystals) and single crystals in a thin layer (unrestricted growth of crystals) is given. The transfer of heat in the measuring cell and the sample and possible errors of experimental results were estimated using the natural scale method.